Fisiologia e fluxo de biomassa em capim-canarana sob pastejo por novilhas com duas frequências e duas intensidades de desfolhação - Chaves, Daniel Rodrigues (2012)
To evaluate the responses of canarana grass erecta lisa (Echinochloa pyramidalis Lam.) grazed by dairy heifers, this study was conduct. Was used a factorial arrangement 2.0 x 2.0 (two frequencies and two defoliation intensity) in completely plots randomized design with five replicates (paddocks). The defoliation frequencies corresponded to interception from 85 and 95% of active photosynthetic radiation and the defoliation intensity corresponded the residual leaf area index 1.0 and 2.0. Were evaluated the growth in regrowth by morphogenesis method, the gas exchange and biomass flow. Were analyzed the growth characteristic: crop growth rate (CGR), relative growth rate (RGR), net assimilate rate (NAR), leaf area ratio (LAR), specific leaf area (SLA), and leaf weight ratio (LWR), also were evaluates: total dry mass forage (TDMF), fresh dry mass forage (FDMF), fresh dry mass leaf (FDML), fresh dry mass stem (FDMS), leaf/stem ratio (L/S). The exchange gas trial were made following measurements: transpiration (E), stomatal conductance (gs), photosynthesis (A), internal CO2/reference CO2 ratio (Ci/CR), efficient use of water (EUW), intrinsic use of water (IUW) and relative index of the chlorophyll (RIC). The variable belonging to biomass flow were: leaf elongation rate (LER), and stem (SER), the elongation rate of the leaf 1/ elongation rate of the leaf 2 (ERL1/ERL2), leaf previous senescence rate (LPVSR), leaf posterior senescence rate (LPOSR) and leaf total senescence rate (LTSR), leafs live number (LLN) and total leafs number (TLN), life leaf time (LLT), leaf appearance rate (LAR) and crop accumulation rate (CAR). The TDMF, FDMF, FDMS and FDML presented increasing values based on age, The L/S ratio showed x. Were obtained increasing values to CGR, and decreasing values RGR, NAR. The values of SFA were increased to 20 days, after showed decreasing values. On the exchange gas trial, there wasn’t difference between management strategies (P>0.05), however on post-grazing the variables EUW and IUW showed lower average (P<0.05), to 85% IAPR. About to cycles of the grazing the evaluates of pre-grazing, the E was lower to 95% IAPR management x intensity 2.0 (P<0.05) The EUW showed lower values to 95% IAPR x intensity 1and higher to 95% x intensity 2 (P<0.05). Evaluates made on post-grazing there was difference to the content of the chlorophyll that showed lower average to intensity 1.0 (P<0.05). On the biomass flow trial, the PVSR, LLN and ALR presented lower values to the less defoliation frequencies (P<0.05), the LPOSR showed lower values to defoliation frequencies. The physiologic characteristic were changed by differences defoliation frequencies and intensity. The growth index of canopy RGR, NAR were committed with the age, but the same not occur to the CGR. The canarana grass should be handled frequently defoliation of 95% interception of photosynthetically active radiation associated whit a residual leaf index 2.0.